2014
DOI: 10.7314/apjcp.2014.15.6.2591
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERCC1, MSH2 and PARP1 in Non-small Cell Lung Cancer and Prognostic Value in Patients Treated with Platinum-based Chemotherapy

Abstract: Purpose: To evaluate the prognostic value of the expression of excision repair cross-complementation group l (ERCC1), MutS protein homolog 2 (MSH2) and poly ADP-ribose polymerase 1 (PARP1) in non-small-cell lung cancer patients receiving platinum-based postoperative adjuvant chemotherapy. Methods: Immunohistochemistry was applied to detect the expression of ERCC1, MSH2 and PARP1 in 111 cases of non-small cell lung cancer paraffin embedded surgical specimens. Through og-rank survival analysis, we evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…PARP-1 expression has been previously demonstrated to be associated with the poor prognosis of numerous tumor types, including early breast cancer and non-small cell lung cancer (13,4042). However, Aiad et al (43) demonstrated that high nuclear PARP-1 expression levels were significantly associated with improved OS in locally advanced breast cancer; Klauschen et al (44) demonstrated that low nuclear expression levels of PARP were associated with a poor prognosis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1 expression has been previously demonstrated to be associated with the poor prognosis of numerous tumor types, including early breast cancer and non-small cell lung cancer (13,4042). However, Aiad et al (43) demonstrated that high nuclear PARP-1 expression levels were significantly associated with improved OS in locally advanced breast cancer; Klauschen et al (44) demonstrated that low nuclear expression levels of PARP were associated with a poor prognosis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer, the leading cause of cancer-related deaths, is one of the most common malignant tumors around the world, of which incidence and mortality have massive growth every year as a result of environmental pollution, excessive cigarette smoking, and second-hand smoke [1]. Importantly, nonsmall-cell lung cancer (NSCLC) is considered to be the major type of lung cancers which occupy approximately 85 % of all lung malignant neoplasms, and the 5-year survival rate remained about 15 % and still has not been increased during the last 30 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide excision repair (NER) and base excision repair (BER) pathway are major DNA repair systems. Besides XRCC1, other DNA base excision repair genes including OGG1, [17] APE1, [17, 3941] XRCC3, [42] PARP1, [43] were reported to be associated with clinical outcomes in NSCLC treated with platinum-based regimen. Genes involved in NER system such as ERCC1 [41, 4345], ERCC2(XPD), [44, 46] BAG1, [46] XPA, [47] were also reported to be associated with clinical outcomes in NSCLC treated with platinum-based regimen.…”
Section: Discussionmentioning
confidence: 99%